Evaluation of airway changes after orthognathic surgery with maxillomandibular advancement or maxillary advancement and mandibular setback - ACAR, YASEMİN BAHAR (My University, 2021)
Introduction/Purpose: The relationship between craniofacial morphology and airway has been well documented in the literature. Surgical changes in jaw positions create reorganization in the surrounding tissues i.e. soft palate, tongue and pharynx; depending on the magnitude and direction of correction. Therefore, oropharyngeal changes caused by orthognathic surgery can affect the airway function. Aim of the present study was to evaluate upper airway changes in two different orthognathic surgery modalities: 1) Bimaxillary Advancement, 2) Maxillary Advancement+Mandibular Setback. Method: Sample in this retrospective study was derived from clinical archive of Orthodontic department in Marmara University. Preoperative (T1) and 6-12 months postoperative (T2) lateral cephalometric radiographies of 24 adult subjects (mean age: 22,3 ± 1,8 years), who underwent bimaxillary orthognathic surgery, were analyzed and superimposed. Direction and amount of horizontal displacement of A-point and B-point were recorded to define surgical movements. Patients were then divided into two groups: Group 1 (n=13) included maxillary advancement+mandibular setback. Group 2 (n=11) included maxillomandibular advancement. Pharyngeal airway changes were measured at posterior (PAS), superoposterior (SPAS), middle (MAS), inferior (IAS) and epiglottic airway spaces (EAS). For intragroup changes Paired sample t-test and Wilcoxon’s test; for intergroup changes Two independent samples t-test and Mann-Whitney U-test were used. Pearson Correlation analysis was performed. Findings: In both groups SNA, SNB,ANB, Wits-Appraisal, Nasion-perpendicular to A-point, maxillary depth values changed significantly. In Group 1, pharyngeal airway changes were nonsignificant. In Group 2 PAS, SPAS, MAS increased significantly and mean pharyngeal airway changes were significantly higher than Group 1. In Group 2, significant and powerful correlation was found between SNB and IAS (r=0,800) and EAS (r=0,719). Conclusion: Mandibular setback did not cause significant reduction in airway when applied in combination with maxillary advancement. Maxillomandibular advancement significantly increased the upper airway parameters and a powerful correlation was observed between SNB and IAS, EAS in this group.
Keywords: Craniofacial morphology; maxillary advancement; mandibular setback; ortognathic surgery